AB0078 THE THERAPEUTIC EFFECT OF GPNMB IN A TRAUMATICALLY-INDUCED OSTEOARTHRITIC MODEL. (June 2019) - Cook, Bryson; Adlaan, Asaad Al; Desanto, Mathew; Safadi, Rama; Frangiamore, Salvatore; Safadi, Fayez
Abstract : Background: Osteoarthritis is a severe joint disease that affects millions of people. At this time, the current treatment for osteoarthritis is total joint reconstruction surgery. GPNMB plays a key role in bone remodeling and bone growth. Data from our lab suggested that GPNMB is positive regulator of osteoblastogenesis and a negative regulator of osteoclastogenesis. Objectives: The role of GPNMB in cartilage has not been investigated before. In this study we examined the therepaeutic effects of GPNMB on damaged cartilage using post-traumatic osteoarthritic mouse model. Methods: The destabilization of the medial meniscus (DMM) surgery in mice has been found to be an excellent model for studying post-traumatic osteoarthritis. We performed the DMM surgery on 21 C57/BL6 mice. These mice were divided into three intra-articular injection treatment groups consisting of a control, low dose GPNMB, and high dose GPNMB. These mice were divided into three intra-articular injection treatment groups consisting of a control, low dose GPNMB, and high dose GPNMB. Moderate to severe osteoarthritis develops around six to eight weeks with this model. Results: Here we present that damaged human cartilage has significantly higher levels of GPNMB compared to undamaged cartilage. In addition, human osteoarthritic chondrocytes treated with GPNMB showed a protective response to inflammation induced by IL1-beta. In this study, we examined whether recombinant GPNMB has an anti-inflammatory effect in a model of post-traumatic osteoarthritis. Based on studies performed in our lab, we expected cartilage degeneration to be dramatically decreased in response to the therapeutic effects of GPNMB. A protective factor against osteoarthritis progression, GPNMB-injected mice had significantly reduced cartilage damage and OARSI scores in comparison to the control group, proving GPNMB a promising therapy in lieu of total joint reconstruction. GPNMB-injected mice also had reduced expression of IL-6 and MMP13 but significantly increased expression of aggrecan in comparison to control mice. Conclusion: Our data clearly showed that GPNMB has therapeutics anti-inflammatory effects on protecting cartilage damaged. Hence, future studies will be directed towards examining the therapeutic effects of GPNMB on larger animal models for osteoarthritis. Given the remarkable ability of GPNMB to reduce expression of key inflammatory markers, we conducted this study to reveal GPNMB therapeutic effects in traumatically-induced osteoarthritis. References: [1] The surgical destabilization of the medial meniscus (DMM) model of osteoarthritis in the 129/SvEv mouse. Methods in Molecular Biology: Osteoporosis and Osteoarthritis. Loeser RF, Goldring SR, Scanzello CR, Goldring MB. Osteoarthritis: A disease of the joint as an organ.Arthritis and Rheumatism. 2012. pp. 1697–1707. [2] Zhou, L., Zhuo, H., Ouyang, H., Liu, Y., Yuan, F., Sun, L., . .. & Liu, H. (2017). Glycoprotein non-metastatic melanoma protein b (Gpnmb) is highly expressed in macrophages of acute injured kidney and promotes M2 macrophages polarization. Cellular immunology, 316, 53-60. [3] Ripoll, V.M., et al., Gpnmb is induced in macrophages by IFN-gamma and lipopolysaccharide and acts as a feedback regulator of proinflammatory responses. J Immunol, 2007. 178(10): p.655766. [4] Karlsson C, Dehne T, Lindahl A, Brittberg M, Pruss A, Sittinger M, Ringe J. Genome-wide expression profiling reveals new candidate genes associated with osteoarthritis. Osteoarthritis and Cartilage. 2010Apr1;18(4):581-92. Disclosure of Interests: None declared